The Context Is the Message: Theory of Indigenous Knowledge Communication Systems. Issue 4 (2nd October 2018) - Manyozo, Linje
Abstract : How should media and communication studies approach the study of indigenous knowledge communication systems (IKCS)? In recent years, there has been a call to dewesternise and decolonise media and communication studies. Many of these debates have focused on rethinking the curriculum and the analytical frameworks and theories therein. This paper seeks to contribute to that debate by arguing for the need to pay attention to IKCS, which continue to shape socio-economic relations in much of the global south. Since the 1960s, there has been an increasing implication of the West and the East in providing development assistance to the global south, which is coincidentally experiencing a rapid exponential growth of the telecommunications and ICT sectors. In these places, however, the spoken word and its orality remain powerful articles and conventions for the generation, exchange and consumption of social meanings and their reference phaneroscopes. The discussion proposes a theoretical framework for studying IKCS. It rejects the location of such systems outside of modernity and contends that indigenous knowledge communications are co-existing with modernity. This critical analysis contributes to the meta-debate on de-centring the enlightenment in media and communications in two ways. First, it discusses an intellectual constitution that has oftentimes been footnoted by dominant media and communication teaching and scholarship. Second, this discussion is framed to undermine the modernistic approaches to media and communication that disregard the ways of speaking and communicating that lie at the periphery of modernity.